Answer:
a = -4 and b = -3
Explanation:
Step 1: Solve 3a + 5b = -27 for a
3a + 5b = -27
3a + 5b + -5b = -27 + -5b
(Add -5b go both sides)
3a = -5b- 27
3a = -5b - 27
3 3
(Divide both sides by 3)
a = -5 b - 9
3
Step 2: Substitute -5 b - 9 for a in 4a + 10b = -46
3
4a + 10b = -46
4(-5 b - 9) + 10b = -46
3
10 b - 36 = -46
3
(Simplify both sodes of the equation)
10 b - 36 + 36 = -46 + 36
3
(Add 36 to both sides)
10 b = -10
3
10/3 b = -10
10/3 10/3
(Divide both sides by 10/3)
b = -3
Step 3: Substitute -3 for b in a = -5/3 b - 9
a = -5/3 (-3) - 9
a = -4
(Simplify both sides of the equation)